2020
DOI: 10.3390/s20185377
|View full text |Cite
|
Sign up to set email alerts
|

Turning Detection During Gait: Algorithm Validation and Influence of Sensor Location and Turning Characteristics in the Classification of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder resulting in a range of mobility deficits affecting gait, balance and turning. In this paper, we present: (i) the development and validation of an algorithm to detect turns during gait; (ii) a method to extract turn characteristics; and (iii) the classification of PD using turn characteristics. Thirty-seven people with PD and 56 controls performed 180-degree turns during an intermittent walking task. Inertial measurement units were attached to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…Turns were identified by the Mobility Lab software, where the angular velocity about the vertical axis exceeded a threshold of 15 • / s. The start and end of each turn were set to the point where the angular velocity dropped below 5 • / s 16 . For each detected turn, the following features were extracted using the Mobility Lab software: turn angle, duration, turn velocity, steps within turn, and raw accelerometer data of all three sensors 16,29 . For determining the lateral acceleration, the sensor data was reoriented from the sensor body frame into a global reference frame using the orientation estimates provided by the Mobility Lab software 16 .…”
Section: Methods For Measuring Turning Movementsmentioning
confidence: 99%
“…Turns were identified by the Mobility Lab software, where the angular velocity about the vertical axis exceeded a threshold of 15 • / s. The start and end of each turn were set to the point where the angular velocity dropped below 5 • / s 16 . For each detected turn, the following features were extracted using the Mobility Lab software: turn angle, duration, turn velocity, steps within turn, and raw accelerometer data of all three sensors 16,29 . For determining the lateral acceleration, the sensor data was reoriented from the sensor body frame into a global reference frame using the orientation estimates provided by the Mobility Lab software 16 .…”
Section: Methods For Measuring Turning Movementsmentioning
confidence: 99%
“…In addition, some studies were recently conducted to evaluate the optimal combination of turning characteristics for improving the classification and prediction performance of freezers among people with PD [ 12 , 17 , 18 ]. These studies have suggested that the occurrence of FOG while turning is associated with structures [ 12 ] such as the prefrontal areas, central pattern generators in the spinal cord, mesencephalic locomotor region, and executive frontal regions [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling using machine learning algorithms based on data combined with comprehensive turning characteristics was recently conducted [ 21 23 ]. Previous studies have identified the predictors for classification of people with PD as faller and non-faller [ 20 ]; these have determined the optimal combination of turning characteristics to distinguish between people with PD and controls [ 17 , 25 ] as well as categorized people with PD as freezers and non-freezers based on the classifiers [ 18 ]. The studies reported a classification accuracy of approximately 70–98% when logistic regression (LR), random forest (RF), support vector machine (SVM), extreme gradient boosting [ 24 ], probabilistic neural network [ 18 ], recursive feature elimination technique with SVM [ 25 ], and partial least square discriminant analysis [ 17 ] were used for training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearables have been used to assess gait in clinical and free-living conditions [23][24][25][26][27][28][29]. Gait characteristics obtained through signal-processing methods can be used to characterise fallers and non-fallers and these outcomes may be used to inform tailored intervention rehabilitation plans [30].…”
Section: Introductionmentioning
confidence: 99%